2003
DOI: 10.1046/j.1523-1747.2003.12557.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Trafficking of the Desmoplakins in Cultured Darier's Disease Keratinocytes

Abstract: Darier's disease is an autosomal dominantly inherited skin disorder characterized by loss of adhesion between epidermal cells, breakdown of desmosome-keratin filaments, and abnormal keratinization. ATP2A2 has been identified as the causative gene of Darier's disease. This gene encodes the sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA) isoform 2 pump, which transports Ca2+ from the cytosol into the endoplasmic reticulum lumen to maintain a low cytosolic Ca2+ concentration. Using indirect immunofluorescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 35 publications
6
43
2
2
Order By: Relevance
“…In addition, the possibility that aberrant DP localization during desmosome assembly may be due to protein misfolding has been raised (28). While we have not extensively studied the possible role of ER stress, we did not observe any changes in DP expression, overall ER structure, or apoptosis/cell growth in SERCA2-deficient cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the possibility that aberrant DP localization during desmosome assembly may be due to protein misfolding has been raised (28). While we have not extensively studied the possible role of ER stress, we did not observe any changes in DP expression, overall ER structure, or apoptosis/cell growth in SERCA2-deficient cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In DD, the mutations in SERCA2 pumps support the importance of intracellular calcium homeostasis necessary for desmosomal adhesions. 5 A 2003 study using cultured DD keratinocytes found that trafficking in desmoplakin was significantly inhibited. Desmoplakin is a desmosomal component that plays a crucial role in linking DD plaques with cell-to-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that PKCa also promotes desmosome assembly supports the idea that this kinase is important for maintaining a dynamic state, which would allow rapid desmosome remodeling in response to environmental cues. Desmosomes are also defective in patients with Darier's disease who have impaired calcium homeostasis because of mutations in the sarco(endo)plasmic reticulum Ca 2þ -ATPase (SERCA) isoform 2 pump (Sakuntabhai et al 1999;Dhitavat et al 2003). Although these abnormalities were suggested to arise from improper folding of desmoplakin, it also seems possible that alterations in calcium-dependent kinase activity could contribute to the observed defects.…”
Section: Aj Maturation and Assembly Of The Desmosomal Plaquementioning
confidence: 99%